Effect of universal varicella vaccination and behavioral changes against coronavirus disease 2019 pandemic on the incidence of herpes zoster. Issue 3 (December 2021) - Shiraki, Kimiyasu; Toyama, Nozomu; Tanaka, Keiko; Ito, Akiko; Yamamoto, Junko; ,
Highlights: Universal varicella vaccination reduced HZ incidence in vaccine recipients. Varicella vaccination increased the HZ incidence among those aged 10–59 years. Varicella vaccination did not affect the HZ incidence among those aged ≥ 60 years. Lifestyle changes due to the COVID-19 pandemic did not affect the HZ incidence. Preventive effects of varicella on HZ is longer than that of Oka varicella vaccine. Abstract: Background: Since 2014, universal varicella vaccination has reduced the varicella and herpes zoster (HZ) incidence in vaccine recipients and increased the incidence in the child-rearing generation until 2017. Objective: This study aimed to understand the future epidemiologic trends of HZ after the disappearance of varicella epidemics and during the coronavirus disease 2019 (COVID-19) pandemic. Methods: The Miyazaki Dermatologist Society has been monitoring and analyzing the incidence of HZ patients after universal vaccination since 1997. Results: The HZ incidence in Oka varicella vaccine recipients aged 0–4 years decreased with the reduction in chickenpox incidence. The HZ incidence among those aged 5–9 years increased between 2015 and 2017 and decreased thereafter. From 2014–2020, the HZ incidence continued to increase to 36.6%, 51.3%, 70.2%, 56.7%, and 27.3% among those aged 10–19, 20–29, 30–39, 40–49, and 50–59 years, respectively. The HZ incidence in patients aged ≥ 60 years increased by 2.3% annually from 2014 to 2020, corresponding to an annual 2% increase since 1997, and was unaffected by varicella epidemics. COVID-19 infection control measures, lifestyle changes and the resulting stress did not affect the HZ incidence in 2020. Conclusion: Universal varicella vaccination eliminated varicella epidemics, and HZ was reduced in vaccine recipients. The HZ incidence for those aged 10–59 years increased from 2014 to 2020, in contrast to those aged ≥ 60 years, which is attributable to booster immunity expiration due to varicella contact in this age group.